A Case of Disseminated Neonatal Varicella Infection: A Challenge to Treat - Mannan, Shamsun Nahar Bintha; Akhter, Feroza; Bakul, Kohinur A; Aurin, Bibi H (Journal of Brahmanbaria Medical College, 2026)
Background: Varicella infection caused by varicella zoster virus can occur in intraurerine life and in neonate if mother is infected with the virus.The characteristic skin lesions are vesicular eruption at the hairline with caudal spread from the head to the trunk and extremities giving a centripetal distribution and pruritus followed by a prodrome of fever, malaise, headache and myalgias. The aim and objectives of this case report is to aware about severe complications of varicella infection in neonate which require early diagnosis and prompt management. Case Presentation: We report a case of neonatal varicella where the mother was having vesicular skin eruptions two days prior to the time of delivery and the neonate contracted it during the perinatal period and developed clinical disease on the twelveth day of life complains of skin eruptions with fluid filled lesions all over the body associated with fever and poor feeding, excessive cry and respiratory difficulty for 2 days. Metabolic acidosis, hypoalbuminaemia, impetigo and abscesses, bacteraemia, pneumonia complicate the patient. Specific anti-viral therapy, intravenous immunoglobulin, intravenous albumin, electrolytes were given. early diagnosis and prompt management save the life of the patient. Conclusion: Maternal varicella infection just before delivery has higher risk of developing neonatal varicella infection which can be disseminated and fetal. Early diagnosis and prompt management, prophylactic treatment to neonatal are the key to save patient from complications and disseminations. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 45-48